'I just want to be normal' – A qualitative study of pregnant women's blogs who present themselves as overweight or obese. (June 2017) - Lingetun, Lovisa; Fungbrant, Madicken; Claesson, Ing-Marie; Baggens, Christina
Abstract: Objective: to describe what pregnant women who present themselves as overweight or obese write about their pregnancy in their blogs. Setting: Swedish private blogs. Design: a qualitative study, using 13 Internet blogs as the source of data. Google was used to find the blogs. The blog content was analysed using thematic analysis. Findings: three main themes were identified: Pregnancy as an excuse, Perspectives on the pregnant body and Becoming a mother. The pregnancy was used as an excuse for breaking the norms, 'I am normal because I am pregnant', and gaining weight, 'I normalise my weight and weight gain'. The women expressed different perspectives of their body through ' For me it is important to look pregnant', 'How others seem to see me' and 'Labelled a risk pregnancy at the antenatal care'. The transition to motherhood was described in 'How the pregnancy affects my life', and there was disappointment when the women experienced 'Unmet expectations'. Key conclusion: the women described themselves as normal behind the obesity and saw their pregnancy as an excuse for their body size and behaviour. They did not identify themselves as a risk group and they did not recognise the midwife's support during the pregnancy. Implication for practice: midwives may have to address overweight and obese pregnant women's attitude towards weight and weight gain in weight gain interventions.